Ventilation/Perfusion Mismatch in Pulmonary Vein Stenosis Secondary to Atrial Fibrillation Ablation - Bollos, Leah Anne Christine L; Kasai, Ryosuke; Otsuka, Hideki; Otomi, Yoichi; Matsuura, Tomomi; Otani, Tamaki; Yamaguchi, Koji; Bando, Takanori; Ueki, Yuya; Matsuda, Noritake; Takashi, Satoru; Azane, Shota; et al. (Asia Oceania journal of nuclear medicine & biology, 2025)
We present two patients with a history of paroxysmal atrial fibrillation who developed pulmonary vein stenosis (PVS) following atrial fibrillation (AF) ablation. Case 1 involved a female patient in her 50s who was asymptomatic for pulmonary symptoms but was found to have a high degree of left superior PVS 15 months after AF ablation. This was demonstrated using contrast-enhanced computed tomography (CE-CT) and supported by findings of perfusion defects on ventilation-perfusion (V/Q) scan. Case 2 was a male patient in his 60s who developed progressive left superior PVS nine months after AF ablation, evidenced by serial CE-CT and V/Q scans. PVS is a rare but well-known complication of pulmonary vein ablation for the treatment of AF that can lead to severe complications if left untreated. V/Q scans effectively assess the functional significance of PVS by detecting abnormal blood flow segments. Although a V/Q mismatch characterized by reduced perfusion defects is more commonly used in evaluating pulmonary embolism, PVS should not be disregarded as a differential diagnosis. Few studies emphasize the utility of V/Q scans in managing PVS and highlight V/Q mismatch as a notable finding. This case report aimed to highlight their significance.